Lesions of the Tongue in the Educational Perspective in the Holy Quran And the Sunnah of the Prophet - A Graphic Study- - Hussein , Sabah (Islamic Sciences Journal, 2023)
ABSTRACT Tongue pests are among the most dangerous pests for humans, because it is easy for a person to be careful and guard against eating unlawful things, injustice, adultery, theft, drinking alcohol, forbidden looking, and other things. It is difficult for him to guard and guard against the movement of his tongue, until you see a man referred to: religion, asceticism, and worship while he speaks words out of anger Allah does not pay any attention to it, He descends into the Fire with one word of it farther than between the East and the West, or plunges it into the Fire for seventy years, How often do you see a man who refrains from immorality and injustice, whose tongue is cut off and slaughtered in honor of the living and the dead, and who does not care about what he says.